A rhetorical analysis of Philippians 1:1-11 - A. H. Snyman (Acta Theologica)
The aim of this article is to analyse Philippians 1:1-11 from a rhetorical perspective that differs from the typical approach of researchers, who tend to force ancient rhetorical categories on a letter. The analysis is done in terms of what is called a “grounded theoretical approach”. This approach is briefly summarised, followed by a systematic analysis of Paul’s basic rhetorical strategy, as well as  of all the supportive rhetorical techniques, in these eleven verses. It will be argued that these verses are not to be regarded as the exordium of the letter, preparing the audience for the “real” arguments later on in the probatio (2:1-3:21). They are part of Paul’s rhetorical strategy in the letter, constructed from the text itself and aimed at persuading his fellow-Christians to persevere in proclaiming and living the gospel that they received at the founding of the church in Philippi. The conclusion is that such a text-centred approach (where the focus shifts from the formal to the functional) provides a better understanding of Paul’s rhetorical strategy in Philippians 1:1-11 than a typical rhetorical analysis, according to which this section forms part of the exordium of the letter.